Turtle Nesting and Conservation Management in Amping Parak, West Sumatra - Sandova, Zettyra; Widuri, Firly; Rizky, Aulia; Yanti, Fauri Yatul Irfan; Nurdin, Jabang; Novarino, Wilson; Aprizal, Aprizal (Jurnal Biologi Tropis, 2026)
Sea turtles are protected marine animals that play a crucial role in maintaining the balance of coastal and marine ecosystems. This study aims to examine the nesting behavior of sea turtles and evaluate the management of the conservation area in Amping Parak, Pesisir Selatan Regency. Conducted from April 15 to May 28, 2026, this research employed a qualitative descriptive method utilizing observation and literature reviews. The results indicate that turtles nest at night, with an incubation period of 45–60 days, which is strongly influenced by nest temperature and humidity. Although Amping Parak has high potential as a nesting habitat, its management is hindered by limited funding and resources. Therefore, optimizing conservation efforts requires nest protection, semi-natural hatchery practices, and community education to ensure the sustainability of sea turtle conservation.